Problems of Students in the Early Childhood to Elementary School Transition Period - Novitawati, Novitawati; Permata Sari, Nina; Hayati, Firdha; Andri Setiawan, Muhammad (Journal of English Language and Education, 2025)
This study aims to determine the difficulties of children who are in the early stages of elementary school and the efforts made by teachers to overcome them. Factors that cause difficulties for children who are in the transition period of ECE SD are internal and external factors, including the lack of synchronization of the SD and ECE curriculum. The research method used is descriptive qualitative with a phenomenological approach. In this study, the instrument used was an interview guide. And the analysis used descriptive analysis. The results of this study indicate that children's learning difficulties were found in the aspects of reading, writing and arithmetic, social, emotional, psychological, and physical-motor. This will have an impact on children so that children will have difficulty learning at the elementary school level. Based on the findings, the efforts made by teachers are 1) collaborating and communicating with parents, 2) helping to direct children both in academics and socializing, 3) using differentiated learning by dividing into three groups according to their respective levels, 4) habituation, 5) activating the class with ice breaking, 6) providing free activities, 7) providing advice,  and 8) establishing cooperation with other teachers. The teacher hopes that after these efforts are made, children can become more independent and can adjust to elementary school.